2004
DOI: 10.1002/jnr.20092
|View full text |Cite
|
Sign up to set email alerts
|

Antipsychotics increase microtubule‐associated protein 2 mRNA but not spinophilin mRNA in rat hippocampus and cortex

Abstract: Antipsychotic (neuroleptic) drugs induce structural alterations in synaptic terminals and changes in the expression of presynaptic protein genes. Whether there are also changes in corresponding postsynaptic (dendritic) markers has not been determined. We describe the effect of 14-day treatment with typical (haloperidol, chlorpromazine) or atypical (clozapine, olanzapine, risperidone) antipsychotics on the expression of two dendritic protein genes, microtubule-associated protein 2 (MAP2) and spinophilin, using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 66 publications
2
22
0
Order By: Relevance
“…In agreement with previous reports in rats (Law et al, 2004a) and humans (Law et al, 2004b), the distribution of spinophilin mRNA in mutant and wild type mice was consistent with a dendritic localization, with labelling observed not only over the pyramidal cell layer, but also adjacent strata of the DG and Ammon's horn. Genotype (F 2, 110 =22.28, P<0.001) had a significant effect upon spinophilin mRNA in the overall ANOVA, and there was a significant genotype by area interaction (F 14, 110 =4.03, P<0.001).…”
Section: Spinophilin Mrnasupporting
confidence: 92%
“…In agreement with previous reports in rats (Law et al, 2004a) and humans (Law et al, 2004b), the distribution of spinophilin mRNA in mutant and wild type mice was consistent with a dendritic localization, with labelling observed not only over the pyramidal cell layer, but also adjacent strata of the DG and Ammon's horn. Genotype (F 2, 110 =22.28, P<0.001) had a significant effect upon spinophilin mRNA in the overall ANOVA, and there was a significant genotype by area interaction (F 14, 110 =4.03, P<0.001).…”
Section: Spinophilin Mrnasupporting
confidence: 92%
“…These findings appear to be consistent with a previous report that the expression of spinophilin mRNA, a protein present in most dendritic spines, was unchanged in rats exposed to antipsychotic medications. 33 Second, the observed decrease in mRNA expression in the subjects with schizophrenia does not appear to reflect a general decline in RNA integrity in these subjects because (1) their brain pH and RIN values were in the range known to be associated with sudden death and good RNA preservation 30 and (2) similar studies in the same subjects with schizophrenia demonstrated no differ- Figure 2 Representative film autoradiograms illustrating the expression of Cdc42, Rac1, RhoA, Duo and drebrin mRNAs in DLPFC area 9 of a control subject and an age-, sex-and PMI-matched subject with schizophrenia. The intensities of the hybridization signals are presented in pseudocolor manner according to the calibration scales (right) for each mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have examined the effect of antipsychotic exposure on spinophilin mRNA or protein expression. Law et al (2004a) reported no change in spinophilin mRNA expression in occipitoparietal cortex and hippocampus of rats after 14 days of daily exposure to chlorpromazine 15 mg/kg, haloperidol 1 mg/kg, clozapine 25 mg/kg, olanzapine 5 mg/kg, or risperidone 0.5 mg/kg. Kabbani and Levenson (2006) examined mice exposed for 16 days to daily haloperidol 3 mg/kg or clozapine 4 mg/kg.…”
Section: Effect Of Antipsychotic Treatmentmentioning
confidence: 96%